Factor Substitution and Effective Tariff Rates - Grubel, H. G.; Lloyd, P. J. (Review of Economic Studies, 1971)
H. G. Grubel, P. J. Lloyd; Factor Substitution and Effective Tariff Rates12, The Review of Economic Studies, Volume 38, Issue 1, 1 January 1971, Pages 95–1